2019
DOI: 10.3389/fpsyt.2019.00046
|View full text |Cite
|
Sign up to set email alerts
|

Stigma of Mental Illness in Germans and Turkish Immigrants in Germany: The Effect of Causal Beliefs

Abstract: Background: Stigma poses an additional burden for people suffering from mental illness, one that often impairs their social participation and can prevent them from seeking adequate help. It is therefore crucial to understand how stigma develops in order to counteract it by setting up effective evidence-based anti-stigma interventions. The present study examines the effect of causal beliefs on stigmatizing behavioral intentions, namely people's desire to distance themselves from persons with mental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 74 publications
(129 reference statements)
2
13
0
1
Order By: Relevance
“…G Endorsing a psychosocial stress model decreases the perceived dangerousness of people with a mental disorder (Schnyder et al, 2018). H Schizophrenia is more likely attributed to a biological model than depression (Angermeyer et al, 2015;Dietrich et al, 2004;Von Lersner et al, 2019). I Depression is more often correctly labelled than schizophrenia (Furnham et al, 2009;Jorm et al, 1997) BEAR study and the add-on study.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…G Endorsing a psychosocial stress model decreases the perceived dangerousness of people with a mental disorder (Schnyder et al, 2018). H Schizophrenia is more likely attributed to a biological model than depression (Angermeyer et al, 2015;Dietrich et al, 2004;Von Lersner et al, 2019). I Depression is more often correctly labelled than schizophrenia (Furnham et al, 2009;Jorm et al, 1997) BEAR study and the add-on study.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…As part of MHL-improving campaigns, biological factors have frequently been emphasized as a cause of mental illness, in particular depression or schizophrenia (Pescosolido et al, 2010;Schomerus et al, 2012). Some studies also found that people were more likely to attribute schizophrenia to biological causal factors rather than depression (Angermeyer et al, 2015;Dietrich et al, 2004;Von Lersner et al, 2019). While the resulting higher endorsement of a biological model decreased the perception of psychiatric patients as responsible and blameworthy for their problems (Kvaale et al, 2013;Lebowitz & Appelbaum, 2017), it also increased prognostic pessimism, and the perceived unpredictability and dangerousness, i.e., negative stereotypes (Haslam, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stigma against patients with mental illnesses resulted in social isolation and avoidance to seeking mental care services ( Von Lersner et al., 2019 ). Stigma against patient with mental illness is widespread and patients were blamed for being diagnosed with mental illness, avoided mental care services, and experienced both physical and emotional violence by others ( WHO, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we synonymy use stigmatized individuals as disadvantaged ones because the disadvantage of an individual makes them vulnerable to stigma. For instance, unemployment (Dougherty, Rick, & Moore, 2017;Staiger et al, 2018), health-related issues and psychological disorder (Chan, Lee, & Mak, 2018;Crowe, Averett, & Glass, 2016;Stangl et al, 2019), disability (Bogart, Rosa, & Slepian, 2019), and immigration (Nevin et al, 2018;Von Lersner, 2019). In addition to this, women were considered disadvantaged based on their gender that restricts them to access entrepreneurial resources (Fischer, Reuber, & Dyke, 1993;Marlow & Patton, 2005).…”
Section: R M B Rmentioning
confidence: 99%